Clean and Healthy Living Behavior (Washing Hands with Soap) with a Peer Group Support Approach to the Community - Afandi, Alfid; Nur, Kholid Rosyidi Muhammad; Kurniawan, Dicky Endrian; Kurniyawan, Enggal Hadi (Rajaki of Tulip Medika Publisher, 2023)
Background: Healthy living behavior is an important activity to be carried out by all levels of society at large. So that in carrying out daily activities can avoid diseases caused by a lack of personal hygiene. In the process of carrying out clean and healthy living behavior activities such as washing hands with soap, not a few people feel bored. The side effect that will be obtained because of this activity is a decrease in work motivation from the community. So, it needs a particular activity to overcome this problem. One of the activities that can be carried out is to provide a support system for fellow citizens in carrying out clean and healthy living behaviors, namely washing hands with soap. Objective: To increase an individual health status will particularly impact community groups and the country. Method: This activity is carried out at least once a week by gathering and telling about daily activities, which always start with washing hands. Result: Mutual support between people working more often outside the home can provide new motivation and enthusiasm for doing their job and a clean and healthy lifestyle. Health education with a peer support approach to the community is more interesting. Conclusion: It has more enthusiasts, so the community will be more obedient to the agreed rules, namely carrying out clean and healthy living behavior activities that can optimize the performance of each individual.